PENENTUAN HUBUNGAN ANTARA SUHU KECERAHAN DATA MTSAT DENGAN CURAH HUJAN DATA QMORPH - - Parwati; - Suwarsono; Kusumaning Ayu DS; Mahdi Kartasamita (Indonesian National Institute of Aeronautics and Space (LAPAN), 2009)
The relationship analysis between the brightness temperature from MTSAT-1R and the rainfall from Qmorph have been conducted in this research. The data used in this research are 240 data sets of MTSAT-1R and QMorph for ten days (1-10 February 2009, 00 – 23 UTC). The analysis is based on the MTSAT-1R spatial resolution (5 x 5 km) which covered 621 pixels for Bengawan Solo Water Catchment Area. The statistical analysis used are timeseries, regression-correlation analysis, and marginal analysis. The result showed that there is a significant correlation between the brightness temperature of MTSAT-1R data with the rainfall from QMorph data (r ≥ 0.80 or equal to R2 ≥ 0.65) for 66 % data or around 410 pixels. The brightness temperature tends to decrease with the higher rainfall, except for the Cirrus cloud which has a cooler temperature but not potential to become rain. Based on the marginal analysis of 410 pixels, we have found a power line regression between the QMorph rainfall (mm/hour) and the MTSAT cloud temperature (°K) with R2 = 0.9837. The equation is: Qmorph rainfall = 2. 1025 (MTSAT cloud temperature)-10.256. In order to increase the accuracy, the validation of QMorph data needs to be done by comparing the QMorph with other rainfall data sources and also taking the topography of area into consideration. Key word: Brigthness temperature, Rainfall, MTSAT, QMorph, Coefficient correlation, Marjinal Analysis